My heart is on the ground: the diary of Nannie Little Rose, a Sioux girl - Rinaldi, Ann (New York : Scholastic, 1999)
In the diary account of her life at a government-run Pennsylvania boarding school in 1880, a twelve-year-old Sioux Indian girl reveals a great need to find a way to help her people
Keywords: Dakota Indians -- Fiction; Indians of North America -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Dakota Indians -- Juvenile fiction